PENURIE D’EAU POTABLE DANS LA CITE DE YANONGE EN TERRITOIRE D’ISANGI (RDC). - ASAKA John, ANGONDO; Felix ELANGA ATILAMBISA,; Jadis SENGA YENGA,; Jean ANDRIOZI OMBA,; Type BOKANGA MPUTU,; Salthiel BOYEMBA AYOMBA,; Emmanuel LOMBO ILONGE,; Ivette NYALUSALA IKANDO, (IJRDO - Journal of Social Science and Humanities Research, 2019)
Water is part of the main stakes of the farming governance. As a lot of farming spaces of the sub-Saharan Africa, the city of Yanonge, commercial environment is confronted to many farming challenges to the first rank of which is the fundamental management, the servicing in electricity, the transportation, the evacuation of the garbage but especially the drainage of the worn-out waters and the access to the drinking water.  The water current of the Congo stream consumed by the population of this part of the country is of bad quality.  This survey pursues the following objectives: to determine the reasons of the non drinkable water consumption; to identify caused them by this illness and clear the consequences that ensue some.  Indeed, the Congolese state must understand that in farming environment the national service of farming hydraulics that has for mission to implant the hydraulic works is confronted to serious problems to know the non rehabilitation of the roads and the reticence of the farming population how to consume water coming from well of water arranged. Of where, the Congolese state must consider a politics adapted to the local cultures. This service makes mumble only his/her/its benefit.